Analisis Customer Engagement pada Akun Instagram @Oksigen_Cafe Menggunakan The Circular Model of Some - Fathul Qorib; Asfira Rachmad Rinata; Latif Fianto (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2021)
Malang City is one of the cities that has many cafes for the younger generation. These cafes compete to get consumers through various strategies, such as using Instagram. One of the exciting cafes in Malang is Oxygen Cafe because it is based on the arts, culture, and literature community. This study aims to see the effectiveness of using Instagram @Oksigen_Cafe in maintaining relationships with its customers through the circular model of some from Regina Lutrell, namely, share, optimize, manage, and engage. This study uses a qualitative method, the primary data source in the form of documentation @Oksigen_Cafe, then strengthened by secondary sources in interviews with cafe owners. The results show that this cafe makes maximum use of Instagram by uploading any exciting information (share) and having an empathetic conversation with followers (engage). However, social media optimization still lacks (optimize), including the lack of understanding of how to use marketing tools, both free and paid marketing (manage). The advantages of Instagram @Oksigen_Cafe, especially in the arrangement of feeds and stories that are compact and based on trending moments. In conclusion, @Oxygen_Cafe can grow through Instagram but still lacks in the technical field of social media. This study suggests that @Oxigen_Cafe expands technical understanding of the use of social media to maximize the potential of Instagram as a way to increase customer engagement.